Tests of ex ante versus ex post theories of collateral using private and public information - Berger, Allen N.; Scott Frame, W.; Ioannidou, Vasso (Journal of Financial Economics, 2011)
Collateral is a widely used, but not well understood, debt contracting feature. Two broad strands of theoretical literature explain collateral as arising from the existence of either ex ante private information or ex post incentive problems between borrowers and lenders. However, the extant empirical literature has been unable to isolate each of these effects. This paper attempts to do so using a credit registry that is unique in that it allows the researcher to have access to some private information about borrower risk that is unobserved by the lender. The data also include public information about borrower risk, loan contract terms, and ex post performance for both secured and unsecured loans. The results suggest that the ex post theories of collateral are empirically dominant, although the ex ante theories are also valid for customers with short borrower–lender relations that are relatively unknown to the lender.